Revisiting fruit and vegetable determinants: Evidence from Latin America - Silva, Andres; Astorga, Andrés; Durán-Agüero, Samuel; Domper, Alejandra (Frontiers in Sustainable Food Systems, 2023)
In the last decade, the public health discussion regarding fruit and vegetable (FV) consumption has been dominated by economic and physical accessibility. Using a online survey in four Latin American countries, we found that, even when consuming less than five FV portions a day, most of respondents were satisfied with the current FV consumption level. However, satisfied respondents consumed significantly less FV than unsatisfied ones. In general, the desirable and current consumption FV levels were associated to different sets of determinants, while years of education was relevant in both cases. Finally, in the hypothetical case that unsatisfied respondents would not face any physical or economic access restrictions, unsatisfied respondents would not reach the goal of five FV portions a day. As a consequence, assuming that physical and economics access improved, this would automatically increase FV to reach the five a day recommendation may be inaccurate in some cases. We also need to take mental access into account, we may ask how to improve the desirable level of FVs, and then, how to close to gap between current and desirable FV levels.